2004
DOI: 10.1167/iovs.03-0485
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Connective Tissue Growth Factor after Glaucoma Filtration Surgery in a Rabbit Model

Abstract: These data support the hypothesis that CTGF plays an important role in scarring and wound contracture after GFS. Inhibition of CTGF synthesis or its action may help prevent bleb failure and improve long-term GFS outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…The common clinical practice is to administer either 5-FU postoperatively by subconjunctival injection or MMC intraoperatively by local application. However, treatment with 5-FU and MMC is often associated with serious adverse effects, such as corneal epithelial defects, wound leaks, and hypotony with accompanying vision loss [1][2][3][4] . These problems have stimulated the search for alternative modes of drug delivery and new agents to minimize ocular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common clinical practice is to administer either 5-FU postoperatively by subconjunctival injection or MMC intraoperatively by local application. However, treatment with 5-FU and MMC is often associated with serious adverse effects, such as corneal epithelial defects, wound leaks, and hypotony with accompanying vision loss [1][2][3][4] . These problems have stimulated the search for alternative modes of drug delivery and new agents to minimize ocular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The local use of antiproliferative agents, such as mitomycin C (MMC) and 5-fluorouracil (5-FU), has improved the surgery outcome by preventing cell growth and scar formation. However, the administration of these drugs can result in a variety of toxicities, including wound leakage, corneal erosion and, rarely, necrosis of the corneal stroma and iris, chronic hypotony, corneal stromal neovascularization, and scleral ulceration [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…To address this area of research, several animal models, including rat (10,11), rabbit (12)(13)(14)(15) and monkey (16,17), have been developed to study the clinical and histological scarring response after GFS. The rabbit has, by far, been the most popular animal used for such studies owing to both the relatively large ocular structures, allowing ease of surgical manipulation, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…104 Given its profibrotic tendencies, it became a protein of interest in surgical models, demonstrating increased expression following glaucoma filtration surgery in rabbits and being associated with an elevated risk of bleb failure. 105,106 The putative role of CTGF in human glaucoma pathophysiology was first identified in pseudoexfoliation syndrome, 107,108 and attention soon focused on how CTGF regulates TM matrix deposition, 109,110 cellular tone, 111 and aqueous outflow facility. 112,113 In one promising recent study, the prostaglandin analog fluprostenol was found to mitigate CTGF-induced fibrogenesis in cultured human TM cells.…”
mentioning
confidence: 99%